The royal wedding [compact disc] : the official album. (Decca Records, 2018)
The official album of the Wedding ceremony of Prince Harry and Ms. Meghan Markle. Musicians confirmed to perform at the wedding ceremony include British cellist Sheku Kanneh Mason, Welsh soprano Elin Manahan Thomas, The Choir of St George's Chapel and Christian gospel group The Kingdom Choir. The Orchestra, conducted by Christopher Warren-Green, will be made up of musicians from the BBC National Orchestra of Wales, the English Chamber Orchestra and the Philharmonia. State Trumpeters are drawn from all ranks of the Band of the Household Cavalry, and will provide ceremonial support during the Service at St George's Chapel. The music will be under the direction of James Vivian, Director of Music, St George's Chapel.